HCV-Associated Nephropathies in the Era of Direct Acting Antiviral Agents - Angeletti, Andrea; Cantarelli, Chiara; Cravedi, Paolo (Frontiers in Medicine, 2019)
Hepatitis C virus (HCV) infection is a systemic disorder that frequently associates with extrahepatic manifestations, including nephropathies. Cryoglobulinemia is a typical extrahepatic manifestation of HCV infection that often involves kidneys with a histological pattern of membranoproliferative glomerulonephritis. Other, less common renal diseases related to HCV infection include membranous nephropathy, focal segmental glomerulosclerosis, IgA nephropathy, fibrillary and immunotactoid glomerulopathy. Over the last decades, the advent of direct-acting antiviral therapies has revolutionized treatment of HCV infection, dramatically increasing the rates of viral clearance. In patients where antiviral therapy alone fails to induce renal disease remission add-on B-cell depleting agents represent an alternative to counteract the synthesis of pathogenic antibodies. Immunosuppressive therapies, such as steroids, alkylating agents and plasma exchanges, may still represent an effective option to inhibit immune-complex driven inflammatory response, but the potentially associated increase of HCV replication and worsening of liver disease represent a serious limitation to their use.